Economic evaluation of spondyloarthritis: economic impact of diagnostic delay in Italy - Mennini FS; Viti R; Marcellusi A; Sciattella P; Viapiana O; Rossini M (Dove Medical Press, 2018)
Francesco S Mennini,1,2 Raffaella Viti,1 Andrea Marcellusi,1–3 Paolo Sciattella,1 Ombretta Viapiana,4 Maurizio Rossini4 1Economic Evaluation and HTA (EEHTA), CEIS, Faculty of Economics, University of Rome “Tor Vergata”, Rome, Italy; 2Institute of Leadership and Management in Health, Kingston University, London, UK; 3Consiglio Nazionale delle Ricerche (CNR), Istituto di Richerche sulla Popolazione e le Politiche Sociali (IRPPS), Rome, Italy; 4Rheumatology Unit, Department of Medicine, University of Verona, Verona, Italy Background and aim: Spondyloarthritis (SpA) is a disease that normally affects the axial skeleton. It progressively leads to overall stiffness up to severe postural deformity of rachis and functional impotence. The objective of the study was to quantify, through an economic model, the impact of specialized testing and pharmacological treatments carried out by the National Health Service (NHS) in normal clinical practice, before the patient is diagnosed with SpA in Italy. In line with the analysis objective, the chosen perspective is that of the NHS.Method: The study was conducted by analyzing the Health Search Database – IMS Health Longitudinal Patient Database, from which newly diagnosed SpA patients were identified over the period 1 January 2007 to 31 December 2013. The use of specialist health care services and pharmacological treatments provided to the patients before the final SpA diagnosis were estimated.Results: Through a retrospective analysis of the Health Search Database, 1,084 subjects (aged 25–45 years) were identified. These patients produced an expense of approximately €153,000 in the 3 years prior to a confirmed SpA diagnosis, in terms of specialist check-ups and drugs, presumably not appropriately used due to a lack of diagnosis. If we assume that the Health Search Database is a representative sample of the Italian population, it may be estimated that, in the 3 years prior to SpA diagnosis, over €5.4 million was largely unduly spent in Italy to examine and manage 38,232 newly diagnosed SpA patients, between 2010 and 2013.Conclusion: The costs due to the delay in SpA diagnosis were quantified for the first time in Italy. For this reason, this work represents a contribution for national and regional decision makers to understand the current clinical practice and the economic consequences of a diagnostic delay in the short and medium term. Keywords: spondyloarthritis, cost of illness, direct cost, claims database, Italy